Synthesis, spectroscopy and electrochemical properties of highly soluble fluoro containing phthalocyanines - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
2(3),9(10),16(17),23(24)-Tetrakis-4'-[3,5-bis-(trifluoromethyl)-phenoxy]-phthalocyanines, {M[Pc-beta(OBz-(CF3)(2))(4)]}, (M = Zn(II), Cu(II), Co(II) and Ni(II)) were synthesized and characterized by elemental analysis, FTIR, H-1 NMR, UV-Vis and MS (Maldi-TOF) spectral data. It is shown that the 4-(3,5-bis(trifluoromethyl)-phenoxy) moieties on the periphery affect the solubility, spectroscopic data and electrochemistry of the tetrakis metallophthalocyanines. The cyclic voltammetry and differential pulsed voltammetry of the complexes give well-defined redox couples in harmony with common metallophthalocyanine complexes. Electrochemical studies show that the complexes exhibit stable monoanionic M{Pc-beta-[(OBz-(CF3)(2))(4)]}(1-) dianionic M{Pc-beta-[(OBz-(CF3)(2))(4)]}(2-) and monocationic M{Pc-beta-OBz-(CF3)(2))(4)]}(1+) species during the reduction and oxidation processes. When compared with the unsubstituted analogues, the redox potentials of the complexes shifted to more positive potentials due to the electron-withdrawing fluorine groups. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanines; fluorine; Maldi-TOF; spectroscopy; aggregation; electrochemistry; RECEPTOR FUNCTIONAL PHTHALOCYANINES; METAL-ION BINDING; CROWN-ETHERS; METALLOPHTHALOCYANINES; SUBSTITUENTS; COMPLEXES; WATER